Ab.: Abl: en latín clásico: Caracterización funcional - Hernández Cabrera, Tomás (Fortunatae: Revista canaria de Filología, Cultura y Humanidades Clásicas, 1998)
In this paper the author shows that in classical latin the ab... abl. preposition is a formal mark of the following four Semantics Functions (SF): Source, Timefrom-which, Cause and Agent.